Optimization with Fuzzy Multiple Criteria Decision Making for Integration, Governance, and Management Study Programs - W. Wasis; S. Suparji; Nining Widyah Kusnanik; Unit Three Kartini (Indonesian Journal of Multidiciplinary Research, 2023)
The purpose of this research is to optimize the integrated modeling of master and doctoral study programs in postgraduate faculties with linear scientific fields needed to deal with changes in higher education governance management using Fuzzy Multiple Criteria Decision Making (F-MCDM). In this study, we propose a novelty for the study program integration model by modifying the MCDM model. FMCDM is used to evaluate the performance of forecasting. Thus, it can handle qualitative criteria that are difficult to explain in the form of sharp values. The results obtained are as expected. Fuzzy Multi-Criteria Decision Making (FMCDM) is a decision-making method for determining the best alternative from many alternatives based on certain criteria. As a result, several study programs in Master (Basic Education, Language and Literature Education, Arts and Culture Education, as well as Technology and Vocational Education) and Doctoral programs (Language and Literature Education, Basic Education, as well as Vocational Education) are still in the Management of Postgraduate Management, while there are 24 master and doctoral study programs integrated with faculties. National Universities continue to reform their public service bureaucracy by submitting proposals to become State Universities Legal Entities (known as PTN-BH in Indonesia).